Fridericia resinosa: a new species of Bignoniaceae from Brazil - Kaehler, Miriam (Phytotaxa, 2020)
Fridericia resinosa is a new species from ecotones bordering the Brazilian savannas and Amazon and savannas-Caatinga. The conspicuous petioles and petiolules length, vernicose adaxial surface of the leaflets, and the dark purple to bordeaux corolla, can be used to distinguish this liana species from morphologically close species. A complete description, diagnosis, a line drawing, distribution map, and notes on phenology, conservation status, and comparison to the morphologically related species are provided.